Redefining boundaries: the case of women angel investors in a patriarchal context. Issue 1 (1st January 2022) - Daou, Alain; Talbot, David; Jomaa, Zouhour
ABSTRACT: While angel investment is a vital source of seed capital, evidence suggests that gendered ascriptions leave women at a disadvantage in terms of both the supply and demand for angel finance. With the bulk of research being skewed towards advanced economies, this paper investigates the motivations and implications behind a woman-to-woman angel fund in an Arab patriarchal context and argues for how it is extending the institutional space. Semi-structured interviews conducted with Lebanese women angel investors show that they are driven by the responsibility to empower women economically and legitimize females' entrepreneurial roles at seed level. In turn, the initiative broadens the ecosystem's boundaries on the one hand, while also legitimizing women-led start-ups by giving them a voice and visibility, allowing them to secure additional onboard seed investments. Accordingly, while acknowledging that rebalancing the gender disparity in the entrepreneurial market is not exclusively a women's issue, our findings show that such initiatives could be an entry point for a gradual transformative change in similar patriarchal societies.